Bioprospecting snakehead fish protein concentrate (SFC) as a non non-serumserum-based albumin source for promoting capacitation in bovine sperm - Setiawan, H.; Lertwichaikul, T.; Thongkham, M.; Chuammitri, P.; Sringarm, K.; Intanon, M.; Sathanawongs, A. (Journal of the Indonesian Tropical Animal Agriculture, 2026)
Capacitation is a prerequisite for successful fertilization with albumin as an inevitable component among the oviductal fluid's constituents. Under in vitroenvironments, albumin's function is replaced by serum-based products, which carry the issue of unsustainability, some allergies, and potential trans-mission of transmissible spongiform encephalopathies (TSEs) to the unborn fetus. To discover an alter-native, sustainable, and innoxious promoter, snakehead fish (Channa striata) albumin was examined for its potential to promote capacitation in bovine sperm. Snakehead fish protein concentrate (SFC) with respective albumin concentrations of 3, 6, and 9 mg/mL was added to the bovine capacitation me-dium. Following the swim-up technique, bovine sperm were incubated in different treatment groups for 90 minutes to stimulate the capacitation process. The results revealed that the application of 3 mg/mL albumin from SFC in Tyrode's-based capacitation medium (T-SFC3) provided sufficient evidence in promoting capacitation, as demonstrated by higher sperm exhibiting hyperactive motility, kinematic parameters, and the percentage of sperm showing B pattern as compared to Tyrode's-based capacitation medium containing 6 mg/mL BSA (T-BSA6) (p>0.05) and other levels of T-SFCs (p<0.05). In con-trast, greater concentrations of SFC application retrieved more viable sperm with intact acrosomes and less in both viable and mortal sperm with reactive acrosomes (p<0.05).